STRATEGI KOMUNIKASI PENYULUHAN DALAM MENUMBUHKAN KESADARAN BERAGAMA PADA KALANGAN REMAJA OLEH ORGANISASI MASJID DI KOTA MEDAN - Alamsyah, Ahmad Gifari; Nugraha, Andhika (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2023)
Juvenile delinquency cases continue to increase, the causes of which vary, ranging from poor association among adolescents, especially in the areas of Al-Ihsan Sidorejo Mosque and Sidorejo Hilir Medan City, lack of parental responsibility in educating their children, disputes with family and with friends, lack of religious understanding among adolescents to lack of public awareness about the importance of cultivating religious awareness for adolescents. This study aims to foster adolescent religious awareness is important to be able to control cases of juvenile delinquency. This research uses strategy theory which is a process of determining the plans of top leaders that focus on the long-term goals of the organization, accompanied by the preparation of a way or effort on how to achieve these goals. And the theory of extension strategy which is a step or action implemented to achieve a target (mission) or goal to be achieved which depends on the extension system, extension approach, type of extension and extension model carried out on the characteristics of the community. This research uses a qualitative approach. The techniques in data collection used are observation, interviews and documentation. While the data analysis technique used is a descriptive data analysis technique. The results of data analysis and research that have been conducted show that the religious awareness counseling strategy carried out by the Islamic Youth organization Al-Ihsan Mosque (HIGMIA) has been running well as HIGMIA's efforts in fostering adolescents in Arinda to grow their religious awareness so as to avoid bad influences in the adolescent environment. Researchers also found that the supporting factors of HIGMIA in implementing the strategy are good BKM that houses the IGMIA, cooperation with various parties and public acceptance of the strategy implemented. While the inhibiting factor is the lack of human resources, the lack of HIGMIA members makes the implementation of the strategy slightly hampered.